2013
DOI: 10.1158/1078-0432.ccr-13-0527
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Kinase Inhibitors, CC214-1 and CC214-2, Preferentially Block the Growth of EGFRvIII-Activated Glioblastomas

Abstract: Purpose mTOR pathway hyperactivation occurs in nearly 90% of glioblastomas, but the allosteric mTOR inhibitor rapamycin has failed in the clinic. Here we examine the efficacy of the newly discovered ATP-competitive mTOR kinase inhibitors CC214-1 and CC214-2 in glioblastoma, identifying molecular determinants of response and mechanisms of resistance, and develop a pharmacological strategy to overcome it. Experimental design We performed in vitro and in vivo studies in glioblastoma cell lines and an intracrani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
3
47
1
Order By: Relevance
“…In agreement with our findings, the dual mTORC1/2 inhibitors CC214-1 and CC214-2 have been recently reported to effectively inhibit growth of GBM cell lines and xenografts resistant to mTORC1 blockade with rapamycin (26). These results support the idea that inhibition of mTORC2 must be achieved for effective blockade of PI3K signaling (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our findings, the dual mTORC1/2 inhibitors CC214-1 and CC214-2 have been recently reported to effectively inhibit growth of GBM cell lines and xenografts resistant to mTORC1 blockade with rapamycin (26). These results support the idea that inhibition of mTORC2 must be achieved for effective blockade of PI3K signaling (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Although Gini and colleagues (26) reported that ectopic expression of the EGFRvIII mutation or PTEN deficiency was necessary to sensitize U87 cells to dual mTORC1/2 inhibition with CC214-2, we found that all BTICs we tested were sensitive to AZD regardless of their underlying endogenous EGFR and PTEN mutational status. Therefore, mTORC1/2 signaling may be a key signaling hub, common to the biology of molecularly diverse GBMs, and provides support for clinical use of mTORC1/2 inhibitors.…”
Section: Discussioncontrasting
confidence: 68%
“…Using gas chromatography-mass spectroscopy (GC/MS) of U87 and U87/EGFRvIII cells treated with mTOR inhibitors (rapamycin or PP242) for 48 hours, we identified 91 metabolites whose levels significantly changed in response to the allosteric mTOR inhibitor rapamycin or the ATPcompetitive mTOR inhibitor PP242 ( Figure 2 and Supplemental Table 1). We have previously shown that rapamycin has minimal activity against mTORC2 signaling in GBM cell lines in in vivo models and patients treated with the drug, whereas PP242 blocks both mTORC1 and mTORC2 signaling in GBM cells (12,13,22). The principal component analysis (PCA) of variation in the metabolites for each treatment group demonstrated distinct clustering or a clear separation of the 3 groups (Supplemental Figure 2, A and B).…”
Section: Introductionmentioning
confidence: 94%
“…As a consequence of EGFR amplification or activating mutation and phosphatase and tensin homolog (PTEN) loss (3,4), hyperactivation of the PI3K pathway is seen in nearly 90% of all GBMs (5,6). As a result, the mechanistic target of rapamycin (mTOR) kinases, a downstream effector, are often constantly hyperactivated (7). mTOR is a central regulator of mRNA translation, metabolism, and autophagy in the cell and, consequently, controls tumor cell growth, survival, and drug resistance (8,9).…”
Section: Glioblastoma (Gbm)mentioning
confidence: 99%